The US film propaganda during the war in Afghanistan - Smaliak, Danila; Rolenc, Jan Martin, 1980-; Halimzai, Pamir; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The war in Afghanistan, initiated in October 2001, has been one of the longest and most contentious conflicts in modern history, marked not only by military engagements but also by a battle of ideologies depicted through media. This thesis investigates US film propaganda during the Afghan War, utilizing discourse and semiotic analysis to scrutinize selected films. The study identifies key propaganda markers: hate speech, emotional appeals, stereotyping, demonization, cruelty or disregard towards one's own people, heroism, opposition, black-and-white thinking, and appeals to nationalism or patriotism. The findings reveal that while some depth is added to characters, the films predominantly portray the American side favorably. This approach reinforces propaganda messages and elicits strong emotional responses, with emotional appeals being the most frequent marker. The propaganda in these films is sophisticated, subtly emphasizing American bravery, heroism, and moral high ground without starkly demonizing the opposition. Elements like demonization, cruelty, and opposition are present but used to create emotional tension rather than overtly negative portrayals. This nuanced approach engages the audience by highlighting American virtues, focusing on positive reinforcement instead of explicit negativity towards the opposition. This strategy shapes public opinion by presenting a compelling narrative that subtly influences perceptions. This analysis enhances the understanding of how cinema serves as a propaganda tool, highlighting its role in shaping societal attitudes towards conflict and military engagement. By dissecting character portrayals, narrative structures, and visual symbolism, the study provides insights into how films may manipulate public opinion and create a certain ideological shift.
Vedoucí práce: Jan Martin Rolenc
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses